O Mercosul ante os mega-acordos regionais: O tema do comércio eletrônico - Marina Amaral Egydio de Carvalho; Marcus Maurer de Salles (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This Discussion Paper identifies the rules on e-commerce provided for in the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), the Regional Comprehensive Economic Partnership (RCEP) and the African Continental Free Trade Area (AfCFTA). Furthermore, the work compares the rules provided for in these mega-agreements with the rules on e-commerce available in the agreements signed by Mercosur internally and with its external partners, as well as relating these rules to those provided for by the World Trade Organization (WTO)
Keywords: K33; F13; F15; F53; 330; mega trade agreements; CPTPP; RCEP; e-commerce; Mercosur; WTO